Diversity of Microbial Eukaryotes Along the West Antarctic Peninsula in Austral Spring - Grattepanche, Jean-David; Jeffrey, Wade H.; Gast, Rebecca J.; Sanders, Robert W. (Frontiers in Microbiology, 2022)
During a cruise from October to November 2019 along the West Antarctic Peninsula between 64.32ºS and 68.37ºS, we assessed the diversity and composition of the active microbial eukaryotic community within three size fractions: micro- (>20µm), nano- (20-5µm), and pico-size fractions (5-0.2µm). The communities and the environmental parameters displayed latitudinal gradients, and we observed a strong similarity in the microbial eukaryotic communities as well as the environmental parameters, between the sub-surface and the deep chlorophyll maximum (DCM) depths. Chlorophyll concentrations were low, and the mixed layer was shallow for most of the 17 stations sampled. The richness of the microplankton was higher in Marguerite Bay (our southernmost stations), compared to more northern stations, while the diversity for the nano- and pico-plankton was relatively stable across latitude. The microplankton communities were dominated by autotrophs, mostly diatoms, while mixotrophs (phototrophs consuming bacteria and kleptoplastidic ciliates; mostly alveolates and cryptophytes) were the most abundant and active members of the nano- and picoplankton communities. While phototrophy was the dominant trophic mode, heterotrophy (mixotrophy, phagotrophy and parasitism) tended to increase southward. Samples from Marguerite Bay showed a distinct community with a high diversity of nanoplankton predators, including spirotrich ciliates and dinoflagellates, while cryptophytes were observed elsewhere. Some lineages were significantly related – either positively or negatively – to ice coverage (e.g., positive for Pelagophyceae, negative for Spirotrichea) and temperature (e.g., positive for Cryptophyceae, negative for Spirotrichea). This suggests that climate changes will have a strong impact on the microbial eukaryotic community.